A Combined Cluster-Chain based Routing Protocol for Lifetime Improvement in WSN - Bensaid, Rahil; Boujemaa, Hatem (International Wireless Communications and Mobile Computing Conference (Online), 2022)
The main challenge in the field of Wireless Sensor Networks (WSNs) is the energy conservation as long as possible. Clustering paradigm has proven its ability to prolong the network lifetime. The present paper proposes a combined cluster-chain algorithm that takes benefit from both cluster based and chain based routing algorithms. Two clustering approaches are proposed and used in the algorithm, namely Kmeans and Fuzzy C-Means methods. First, K -means or FCM technique is used to construct a predefined number of clusters. Second, we apply Power Efficient Gathering in Sensor Information Systems (PEGASIS) protocol to form a local shortest chain in each cluster. A comparison with PEGASIS and Low Energy Adaptive Clustering Hierarchy (LEACH) protocol is presented to analyze the performance and to validate the proposed algorithm. Simulation results showed that the proposed algorithm, consumes less energy and effectively prolongs the network lifetime.